Relationship Between Mothers’ Role and Knowledge in Recurrence Prevention of Food Allergy for Children Under Five Years-Old - Fitria Rinawarti (Jurnal Berkala Epidemiologi, 2017)
There are 30-40% of allergy patients worldwide in 2011. This is in line with data from the Center for Disease Control and Prevention (CDC) which records the incidence of allergies has tripled from 1993 to 2006. Parents are very important to overcome allergic recurrence in children so that allergic relapses do not occur often and do not get a heavier recurrence. The research objective is to analyze the relationship between the role and knowledge of mothers in the prevention of recurrence of food allergies in infants. This research was an observational analytic study using a cross-sectional design. This research was conducted at the Children's Specialist Poly Hospital of Jemursari Islamic Hospital in October 2015 - January 2016. Sampling using a simple random sampling method. The research sample is 39 mothers of children who suffer from food allergies. Data analysis using the chi-square test. The results showed that 15 people (38.5%) had maternal knowledge in preventing recurrence of food allergies in under five years children, while 26 people (66.7%) lacked a good role in preventing allergic recurrence. Statistical test results using chi-square showed that there was a relationship between the role of the mother (ρ = 0.030) and the mother's knowledge (ρ = 0.00001) in the prevention of recurrence of food allergy in infants. The conclusion of the study is that mothers with unfavorable roles have children under five with severe allergic recurrence, while mothers of toddlers with good knowledge have children under five with mild allergic recurrence.